Agrargeographische Beobachtungen im Küstentiefland von Metapont - Rother, Klaus (ERDKUNDE, 1967)
The author reports on some agricultural mapping which he carried out in South Italy in 1965. Based on the threefold morphological division of the coastal region between the north Calabrian upland and the Murge of Apulia into Nehrung, lagoon and gravel plateau zones, the arable dominated pattern of cultivation is described. The observations show that this is primarily determined by ecological relationships. Agro-social factors have only a subordinate significance, because the traditional land-ownership systems of Latifundia and peasant small-holdings, originally clearly separated spatially from one another, are nowadays closely dovetailed, following the Italian agrarian reforms of 1951. In the second section, the consequences of the reforms for settlement and population geography are described. There has been a movement of villages away from the old compact highland sites into the lowland, which is now characterized in the larger more isolated areas by linear Einzelhof settlements with strip fields. Similar to the legislative measures affecting large-scale land ownership, the small sizes of the new farm units (4-8 ha) have resulted in agricultural intensification. In conclusion comment is made upon the insufficient co operative links between the new farmers and the consequent marketing difficulties. Wide ranging market guarantees, guided cultivation programmes and population policy measures, if they took into account the only poorly developed industrialization of the area, could solve the economic and social problems.